Phenolic moulding plastic for lithium battery separator and preparation method thereof

By using medium-molecular and high-molecular-weight thermoplastic phenolic resins, bakelite board powder and wollastonite fibers in phenolic molding materials, combined with ulottropine curing agent, the dimensional instability and heat resistance of phenolic molding materials at high temperatures is solved. The problem of insufficient results has achieved high-performance and low-cost lithium battery separator materials.

CN119161689APending Publication Date: 2024-12-20SHANGHAI EUROPEAN-ASIAN SYNTHETIC MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411422172.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing phenolic molding materials are unstable in size at high temperatures, are prone to warping and deformation, and have insufficient heat resistance, which cannot meet the flatness and insulation performance requirements of lithium battery separators.

Method used

Medium molecular weight and high molecular weight thermoplastic phenolic resins are used as binders, bakewood board powder and high-even-to-diameter wollastonite fibers are used as fillers, and ulotropine is used as curing agents. Combined with curing accelerators, it is mixed by ultrafine pulverization and heating. The refining process improves the heat resistance and rigidity of the material.

Benefits of technology

It significantly improves the dimensional stability and heat resistance of phenolic molding materials at high temperatures, reduces manufacturing costs, and realizes the high performance and environmentally friendly utilization of lithium battery separators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081128420000021
    Figure BDA0005081128420000021
  • Figure BDA0005081128420000051
    Figure BDA0005081128420000051
  • Figure BDA0005081128420000061
    Figure BDA0005081128420000061
Patent Text Reader

Abstract

The invention provides a phenolic moulding compound for a lithium battery separator. The phenolic moulding compound comprises the following raw materials: medium molecular weight thermoplastic phenolic resin, high molecular weight thermoplastic phenolic resin, bakelite plate powder, wollastonite fiber, a urotropine curing agent, a curing accelerator and a release agent. According to the phenolic moulding plastic provided by the invention, the bakelite plate powder is used as a filler instead of wood powder, and a certain amount of high-molecular-weight thermoplastic phenolic resin is added on the basis of adding the medium-molecular-weight thermoplastic phenolic resin under the condition that the preparation processability of the phenolic moulding plastic is not influenced, so that the phenolic moulding plastic has better heat resistance and rigidity; the raw materials are easy to obtain, the preparation process is simple, the cost is relatively low, and the high-temperature dimensional stability of the general phenolic moulding plastic can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a phenolic molding compound for lithium battery separators and a preparation method thereof. Background Art

[0002] Phenolic molding compound is one of the three major thermosetting plastics. It is low in cost and widely used, especially in the fields of household appliances, electrical accessories and mechanical accessories. General phenolic molding compound is generally made of phenolic resin as a binder, wood powder and minerals as fillers, and a curing agent and an accelerator. However, since wood powder contains cellulose, hemicellulose, lignin and other relatively easy-to-flow substances that are soluble in acetone solvents, the heat resistance of phenolic molding compound is insufficient after molding, and it is easy to warp and deform, and cannot meet the flatness requirements of lithium battery separators. Therefore, the relevant technical personnel of our company have done a lot of improvement work on the rigidity of the material and the dimensional stability at high temperatures.

[0003] Lithium battery separators require good insulation performance, stable insulation performance in humid environments, and stable chemical resistance. The product is a thin plate structure and requires high dimensional stability. The product thickness is generally 0.5-10mm and the length is 100-500mm. No warping or deformation should occur during use. The product is required to be halogen-free and have high flame retardant performance (UL V-0 grade).

[0004] Bakelite is a phenolic laminate made of bleached wood pulp paper impregnated with phenolic resin and hot pressed. Paper-based Bakelite is the most common laminate and the most widely used and used industrial laminate in the world. It has good electrical properties at room temperature and good mechanical processing performance. The relative density is about 1.40, the warpage is ≤3‰, and it has excellent electrical, mechanical and processing properties. This product is suitable for use as insulating structural parts in motors and electrical equipment with high mechanical performance requirements, and can be used in transformer oil. It has good mechanical strength and is suitable for PCB industry drilling pads, distribution boxes, fixture boards, mold splints, high and low voltage distribution boxes, packaging machines, combs, etc. It is suitable for motors, mechanical molds, PCBs, ICT fixtures, molding machines, drilling machines, table grinding pads, etc.

[0005] As the national environmental protection regulations have become stricter in the management of waste disposal, a large amount of waste will be generated during the application and processing of bakelite (processing into the required size and shape), which is generally treated as solid waste and incinerated. If bakelite waste can be recycled, it is a favorable measure that is both environmentally friendly and economically beneficial.

[0006] Through continuous and unremitting efforts, the applicant of the present invention uses medium molecular weight thermoplastic phenolic resin and high molecular weight thermoplastic phenolic resin as adhesives, bakelite flour and high aspect ratio wollastonite fiber as fillers, urotropine as a curing agent, and a curing accelerator, so that the material has better rigidity and dimensional stability at high temperature than general phenolic molding materials, and the production process is simple and the manufacturing cost is relatively low. Summary of the invention

[0007] In view of the defects of the prior art, the object of the present invention is to provide a phenolic molding compound for lithium battery separators, which has readily available raw materials, is easy to process and has relatively low cost, and a preparation method thereof.

[0008] To achieve the above purpose, the solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a phenolic molding compound for a lithium battery separator, comprising the following raw materials in percentage by weight:

[0010]

[0011] Preferably, the medium molecular weight thermoplastic phenolic resin has a molar ratio of phenol to formaldehyde of 1:(0.75-0.83), free phenol ≤4.5, water ≤1.0, polymerization speed 30-60S, and fluidity 40-80mm.

[0012] Preferably, the high molecular weight thermoplastic phenolic resin has a molar ratio of phenol to formaldehyde of 1:(0.88-0.92), free phenol ≤4.5, water ≤1.0, a polymerization speed of 20-40S, and a fluidity of 10-30mm.

[0013] Preferably, the bakelite board powder is obtained by crushing bakelite board waste, and has a fineness of 30-200 meshes, and the bakelite board is a phenolic laminated paperboard made by hot-pressing bleached wood pulp paper impregnated with phenolic resin.

[0014] Preferably, the aspect ratio of the wollastonite fiber is 10:1-15:1, and the fineness is 300-1500 mesh.

[0015] Preferably, the curing accelerator is selected from one or more of magnesium oxide, calcium oxide and calcium hydroxide.

[0016] Preferably, the release agent is selected from one or more of calcium stearate, zinc stearate, lithium stearate, stearic acid, stearic acid amide and ethylene bis stearic acid amide.

[0017] According to the present invention, the bakelite board powder used in the present invention is obtained by crushing bakelite board waste, and the fineness is 30-200 mesh. The bakelite board is a phenolic laminated paperboard made by hot pressing bleached wood pulp paper impregnated with phenolic resin. The phenolic resin used for impregnation in bakelite board production is a liquid thermosetting phenolic resin, which has better heat resistance than thermoplastic phenolic resin. A large amount of waste will be generated during the application and processing of bakelite board (processed into the required size and shape). These bakelite board wastes are crushed and recycled to replace wood powder and applied to phenolic molding materials. The heat resistance and rigidity are improved, which is both environmentally friendly and can produce economic benefits. A phenolic molding material for lithium battery separators with relatively low cost and better performance can be obtained.

[0018] According to the present invention, the present invention adopts high molecular weight thermoplastic phenolic resin, the main reason is: the present invention adopts bakelite wood powder instead of wood powder as filler, bakelite is made of bleached wood pulp paper after being impregnated with phenolic resin and then hot pressed, so the oil absorption rate of bakelite wood powder is much lower than that of wood powder, even if high molecular weight phenolic resin is used to replace medium molecular weight phenolic resin, it will not affect the melt viscosity of phenolic molding material (generally measured by torque data in rheological test, low torque, low injection pressure of phenolic molding material, good injection process); and high molecular weight thermoplastic phenolic resin has a larger cross-linking density after reacting with curing agent, and has better heat resistance and rigidity. Therefore, the present invention adopts bakelite wood powder instead of wood powder as filler, and under the condition of not affecting the preparation and processing performance of phenolic molding material, on the basis of adding medium molecular weight thermoplastic phenolic resin, a certain amount of high molecular weight thermoplastic phenolic resin is added, so as to improve the heat resistance and rigidity of phenolic molding material.

[0019] According to the present invention, the wollastonite fiber used in the present invention is a functional mineral fiber, which is processed from selected high-quality wollastonite. Wollastonite is also known as calcium silicate or calcium silicate. The product has good fiber quality and high suspension value. It can partially replace other high-end polymer reinforcement materials such as glass fiber and plant fiber, improve the physical properties of products such as boards, profiles, wood plastics, and building templates, and reduce costs.

[0020] According to the present invention, the hexamethylenetetramine curing agent used in the present invention plays a curing and cross-linking role, thereby enhancing the heat resistance and other properties of the material.

[0021] In a second aspect, the present invention also provides a method for preparing the phenolic molding compound for lithium battery separators as described above, comprising the following steps: firstly ultrafinely grinding the medium molecular weight thermoplastic phenolic resin, the high molecular weight thermoplastic phenolic resin, the urotropine curing agent and the curing accelerator to a fineness of more than 200 meshes, then uniformly mixing the above mixture with other raw materials, heating and mixing or extruding, and finally granulating and forming, so as to obtain the phenolic molding compound for lithium battery separators.

[0022] According to the present invention, in the preparation process of the phenolic molding material for lithium battery separator provided by the present invention, the medium molecular weight thermoplastic phenolic resin, the high molecular weight thermoplastic phenolic resin, the urotropine curing agent and the curing accelerator are firstly ultra-finely crushed to a fineness of more than 200 meshes, so that the cross-linking reaction between the medium molecular weight and high molecular weight phenolic resin and the curing agent is more sufficient, thereby improving the mechanical strength and heat resistance.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The phenolic molding material provided by the present invention adopts bakelite wood powder instead of wood powder as filler, and adds a certain amount of high molecular weight thermoplastic phenolic resin on the basis of adding medium molecular weight thermoplastic phenolic resin without affecting the preparation processability of the phenolic molding material, so that the phenolic molding material has better heat resistance and rigidity; the raw materials are easy to obtain, the preparation process is simple, the cost is relatively low, and the dimensional stability of the general phenolic molding material at high temperature can be greatly improved. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with the embodiments, the purpose of which is to better understand the content of the present invention and embody the essential characteristics of the present invention, so the examples given should not be regarded as limiting the scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention.

[0026] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0027] The manufacturing method of the molding material of the present invention can adopt the conventional twin-roller mixing method or the screw extrusion method.

[0028] Before mixing or extruding, the resin binder including the medium molecular weight thermoplastic phenolic resin and the high molecular weight phenolic resin, the urotropine curing agent and the curing accelerator are pre-ultra-finely crushed and mixed to a fineness of more than 200 meshes, so that the cross-linking reaction between the medium molecular weight and high molecular weight phenolic resin and the curing agent is more sufficient, thereby improving the mechanical strength and heat resistance; then the above mixture is evenly mixed with other raw materials, heated for mixing or extrusion, and finally granulated to obtain the desired product.

[0029] The materials in the formula shown in Table 1 are crushed, mixed, kneaded or extruded according to the above manufacturing method, and finally granulated and formed to obtain the desired product. The formulas and characteristic data of Examples 1-5 and Comparative Example 1 are listed in the table. The formula amounts in the table are all expressed in weight %.

[0030] The test pieces for property evaluation are prepared by compression molding. The performance indexes are measured according to ISO14526-2 standard. The evaluation method is as follows:

[0031] The molding conditions are: preheating temperature: 100-110°C, pressing mold temperature: 170-175°C, and curing time: 1.0min / mm.

[0032] Table 1

[0033]

[0034]

[0035] The materials in Table 1 are annotated as follows:

[0036] (1) Medium molecular weight thermoplastic phenolic resin

[0037] Medium molecular weight thermoplastic phenolic resin, the molar ratio of phenol to formaldehyde is 1: (0.75-0.83), free phenol ≤ 4.5, moisture ≤ 1.0, polymerization speed 30-60S, fluidity 40-80mm. The determination of technical indicators of phenolic resin is carried out according to GB / T 30772-2014 standard.

[0038] (2) High molecular weight thermoplastic phenolic resin

[0039] High molecular weight thermoplastic phenolic resin, the molar ratio of phenol to formaldehyde is 1: (0.88-0.92), free phenol ≤ 4.5, moisture ≤ 1.0, polymerization speed 20-40S, fluidity 10-30mm. The determination of technical indicators of phenolic resin is carried out according to GB / T 30772-2014 standard.

[0040] (3) Bakelite Powder

[0041] Bakelite powder, 80 mesh.

[0042] (4) Wollastonite fiber

[0043] Wollastonite fiber, aspect ratio 10:1-15:1, 800 mesh, Jiangxi Aote Fine Powder Co., Ltd.

[0044] As can be seen from Table 1, the raw materials of Examples 1-5 are all in accordance with the ratio specified in the present invention, using medium molecular weight thermoplastic phenolic resin and high molecular weight thermoplastic phenolic resin as adhesives, bakelite flour and high aspect ratio wollastonite fiber as fillers, urotropine as curing agent, and a curing accelerator. The phenolic molding plastic samples produced have a flat surface after baking (180°C / 6 hours), and the heat deformation temperature (about 180°C) is also relatively high. However, the phenolic molding samples produced in Comparative Example 1 have warped surfaces after baking (180°C / 6 hours), and the heat deformation temperature is relatively low (about 160°C). It can be seen that the materials produced by the scheme of the present invention greatly improve the rigidity and dimensional stability of general phenolic molding plastics at high temperatures.

[0045] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A phenolic molding compound for lithium battery separator, characterized in that: The raw materials include the following weight percentages:

2. The phenolic molding compound for lithium battery separator according to claim 1, characterized in that: The medium molecular weight thermoplastic phenolic resin has a molar ratio of phenol to formaldehyde of 1:(0.75-0.83), free phenol ≤4.5, water ≤1.0, a polymerization speed of 30-60S, and a fluidity of 40-80mm.

3. The phenolic molding compound for lithium battery separator according to claim 1, characterized in that: The high molecular weight thermoplastic phenolic resin has a molar ratio of phenol to formaldehyde of 1: (0.88-0.92), free phenol ≤4.5, water ≤1.0, a polymerization speed of 20-40S, and a fluidity of 10-30mm.

4. The phenolic molding compound for lithium battery separator according to claim 1, characterized in that: The bakelite board powder is obtained by crushing bakelite board waste, and the fineness is 30-200 meshes. The bakelite board is a phenolic laminated paperboard made by hot pressing bleached wood pulp paper impregnated with phenolic resin.

5. The phenolic molding compound for lithium battery separator according to claim 1, characterized in that: The aspect ratio of the wollastonite fiber is 10:1-15:1, and the fineness is 300-1500 meshes.

6. The phenolic molding compound for lithium battery separator according to claim 1, characterized in that: The curing accelerator is selected from one or more of magnesium oxide, calcium oxide and calcium hydroxide.

7. The phenolic molding compound for lithium battery separator according to claim 1, characterized in that: The release agent is selected from one or more of calcium stearate, zinc stearate, lithium stearate, stearic acid, stearic acid amide and ethylene bis stearic acid amide.

8. A method for preparing a phenolic molding compound for lithium battery separator according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: firstly, ultra-finely grinding medium molecular weight thermoplastic phenolic resin, high molecular weight thermoplastic phenolic resin, urotropine curing agent and curing accelerator to a fineness of more than 200 meshes, then uniformly mixing the mixture with other raw materials, heating and kneading or extruding, and finally granulating and forming, so as to obtain the phenolic molding material for lithium battery separator.